2011
DOI: 10.1002/jmv.22139
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of disease severity between genotypes IA and IIIA of hepatitis A virus

Abstract: Although hepatitis A is a major health problem worldwide, it has not yet been clarified whether or not viral factors affect the clinical characteristics. This study aimed to investigate if a genotype of hepatitis A virus (HAV) affects disease severity among adolescent and adult populations. Clinical data and specimens were collected from patients ≥16-years-of-age with acute hepatitis A at two university hospitals in Korea during the two study periods: 1998 and 1999 (n = 45), and 2009 (n = 66). Nucleotide seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…In the present study, the mean age of subgenotype IA and IIIA patients was 49 ± 9.6 and 49.5 ± 27.5 years, respectively. A recent study from Korea reported that HAV genotype influences the severity of liver disease and that a higher ALT level (>1000 IU/L) and longer hospitalization were significantly associated with subgenotype IIIA 7 . All HAV‐associated acute liver failure patients in the study of Fujiwara et al 4 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the present study, the mean age of subgenotype IA and IIIA patients was 49 ± 9.6 and 49.5 ± 27.5 years, respectively. A recent study from Korea reported that HAV genotype influences the severity of liver disease and that a higher ALT level (>1000 IU/L) and longer hospitalization were significantly associated with subgenotype IIIA 7 . All HAV‐associated acute liver failure patients in the study of Fujiwara et al 4 .…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that almost all acute hepatitis A cases (93.6%) were caused by subgenotype IA and only 2.1% by subgenotype IIIA, 4 and that all acute liver failures were caused by subgenotype IA. Thus, the possibility of a changing pattern in circulating HAV genotypes such as that reported in Korea 7 might need to be entertained in Japan as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previouse studies on HAV genotypes in Republic of Korea have shown a distinct changing pattern in circulating HAV genotypes over the past 10 years [24]. Until 2004, subgenotype IA was the most prevalent in the Republic of Korea [25].…”
Section: Introductionmentioning
confidence: 99%